Media "Exploading Box" IPAS Differentiated Based on Ethnoscience: A Solution to Optimize Science Literacy - Sulthonia, Aqthora; Sayekti, Ika Candra (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to develop and assess the feasibility of ethnoscience-based exploding box learning media that incorporates batik activities to enhance science literacy among elementary school students. Methodology: The research applies a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), though limited to the development phase. Data were collected through observation, interviews, documentation, and questionnaires. Qualitative analysis was conducted using feedback from media and content experts, while quantitative data were obtained from expert validation questionnaires. Results: The resulting exploding box media integrated into IPAS learning on the topic of changes in the states of matter for fourth-grade students received an average validation score of 88.23% from media experts and 95% from material experts, both categorized as “very worthy. Applications/Originality/Value: Rooted in the ethnoscientific context of Surakarta’s batik tradition, this media supports differentiated instruction by catering to visual, auditory, and kinesthetic learning styles. It serves as a culturally responsive innovation that promotes early science literacy through engaging and contextually relevant learning experiences.